2016
DOI: 10.1002/cm.21308
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the fibroblast cytoskeletal architecture during the replication cycle of Ectromelia virus: A morphological in vitro study in a murine cell line

Abstract: Ectromelia virus (ECTV, the causative agent of mousepox), which represents the same genus as variola virus (VARV, the agent responsible for smallpox in humans), has served for years as a model virus for studying mechanisms of poxvirus-induced disease. Despite increasing knowledge on the interaction between ECTV and its natural host-the mouse-surprisingly, still little is known about the cell biology of ECTV infection. Because pathogen interaction with the cytoskeleton is still a growing area of research in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 55 publications
6
23
0
Order By: Relevance
“…Infected cells exhibited multiple irregular long cellular extensions, similar to those previously observed in ECTV-infected L929 fibroblasts [27]. Although VACV and CPXV have been shown to induce morphological changes of DCs, these viruses do not stimulate formation of long cytoskeletal protrusions in infected cells [22,38].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Infected cells exhibited multiple irregular long cellular extensions, similar to those previously observed in ECTV-infected L929 fibroblasts [27]. Although VACV and CPXV have been shown to induce morphological changes of DCs, these viruses do not stimulate formation of long cytoskeletal protrusions in infected cells [22,38].…”
Section: Discussionsupporting
confidence: 55%
“…At the late stage (24 hpi) of infection with live-ECTV, majority of the infected cells had larger, but still regular viral factories and numerous progeny virions located near the viral factories and within cellular extensions, formed extensively by infected cells (Fig 1A). Presence of multiple cellular extensions gave the cells a unique, multifaceted morphology, previously observed in ECTV-infected L929 fibroblasts [27]. Moreover, at 24 hpi viral factories in infected GM-BM were strongly stained with anti-ECTV pAbs, suggesting that the quantity of antigens recognized by those antibodies increased together with the progress of virus replication.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The following mAbs were used for cytokine detection: anti-tumor necrosis factor (TNF)-FITC (MP6-XT22, rat IgG1), anti-IL-12(p40/p70)-APC (C15.6, rat IgG1; both from BD Biosciences) and anti-CCL3 [macrophage inflammatory protein 1 alpha (MIP-1α)]-PE (DNT3CC; rat IgG2a; eBioscience, San Diego, CA, United States). In some experiments, cells were stained intracellularly for the presence of ECTV antigens using a Cytofix/Cytoperm kit and rabbit polyclonal Abs anti-ECTV-FITC, obtained as previously described ( Szulc-Dabrowska et al, 2016 ). The staining procedure also included appropriate isotype controls obtained from BD Biosciences and eBioscience.…”
Section: Methodsmentioning
confidence: 99%
“…This unique feature requires intracellular reorganization of the cytoskeleton and organelles, including mitochondria, endoplasmic reticulum, lysosomes, endosomes, and Golgi apparatus [ 22 ]. Our previous study indicated that ECTV infection leads to cytoskeletal rearrangement and alterations in mitochondrial network morphology and distribution in established cell lines [ 23 , 24 , 25 ]. In the present study, we asked how ECTV infection affects mitochondrial network morphology and physiology in permissive cells.…”
Section: Introductionmentioning
confidence: 99%